Desenvolvimento de suplemento alimentar calórico proteico pronto para uso a base de baru (Dipteryx Alata), hidrolisado protéico de semente de melancia (Crimson Sweet) e inajá (Maximiliana Maripa) - Oliveira, Lais Gama de (Universidade Federal do Tocantins, 2024)
The inajá palm tree has edible nut fruit with a high lipid content, but with reduced amounts of proteins. Watermelon seed cake then emerges as an option for a vegetable source of protein and the production of protein hydrolysates. The objective of this work was to develop an energy-protein supplement characterized as Read to use food (RUF) based on inajá oil and watermelon seed protein hydrolyzate (TSM). The TSM hydrolysis conditions were evaluated using the commercial enzyme bromelain. For this, a central composite rotational design (DCCR) was adopted, evaluating the influence of the independent variables time, temperature and enzyme concentration on the degree of hydrolysis and antioxidant activity evaluated by the DPPH, FRAP and ABTS protocols. The best assay was used to prepare four formulations with different concentrations of hydrolyzate: F1 (20%); F2(25%); F3(30%); F4(35%). The yield, nutritional composition and technological properties of the hydrolyzate were analyzed. The formulations were analyzed for nutritional composition, vitamin content, total phenolic compounds, minerals and fatty acids. The sensory analysis was carried out using an affective test (acceptance and purchase intention) and CATA descriptors. The best hydrolysis condition was obtained when the watermelon seed cake was subjected to the hydrolytic process with an enzyme concentration of 1%, for 120 minutes at 60ºC. This assay was chosen for the production of the hydrolyzate. The mixed fraction of the hydrolyzate showed 83.45% yield, 48.7% protein and 23.63% solubility. The four formulations prepared presented 25 to 28.9% proteins, 28.61 to 31.48% lipids, 477.97 to 507 Kcal. The four formulations had vitamin C and E in their composition, however vitamin A values were not determined. Regarding mineral content, the formulations highlighted Iron, Zinc and Manganese, meeting 30 to 70% of the recommended daily value. . The affective sensory tests showed that the formulations require adjustments in terms of flavor to meet the expectations generated by the appearance and aroma of the product. Flavor was the attribute with the greatest impact on panelists' acceptance. Formulation 4, with the highest percentage of hydrolyzate, had a bitter taste, differing from the others. The acceptability index indicated that aroma, appearance and color were the attributes approved by the tasters with values above 70%.